2005
DOI: 10.1136/ard.2004.028670
|View full text |Cite
|
Sign up to set email alerts
|

Body weight, body composition, and bone turnover changes in patients with spondyloarthropathy receiving anti-tumour necrosis factor   treatment

Abstract: Objectives: To determine the changes in body weight, body composition, and bone turnover in patients with spondyloarthropathy (SpA) treated with anti-tumour necrosis factor a (TNFa). Patients and methods: 19 patients with SpA (2 women, 17 men), aged 21-71 years, were studied in a 1 year prospective open study. 17 patients received infliximab: 3 or 5 mg/kg/infusion at weeks 0, 2, 6 and infusions in the case of a relapse (n = 14) or systematically (n = 3); 2 patients received etanercept (25 mg twice a week). Bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
136
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(149 citation statements)
references
References 31 publications
12
136
0
1
Order By: Relevance
“…Inflammation may influence bone metabolism due to the effect of pro-inflammatory mediators such as interleukin-1, interleukin-6, and tumor necrosis factor-alpha, which play an important role in bone loss through their effect on osteoclast activity [14]. The most suggestive findings that inflammation contributes to bone loss in the spine come indirectly from studies confirming that in patients receiving anti TNF therapy there is not only a significant improvement of symptoms and a decrease of inflammation, but also an increase in BMD [15][16][17][18].…”
Section: Discussionmentioning
confidence: 74%
“…Inflammation may influence bone metabolism due to the effect of pro-inflammatory mediators such as interleukin-1, interleukin-6, and tumor necrosis factor-alpha, which play an important role in bone loss through their effect on osteoclast activity [14]. The most suggestive findings that inflammation contributes to bone loss in the spine come indirectly from studies confirming that in patients receiving anti TNF therapy there is not only a significant improvement of symptoms and a decrease of inflammation, but also an increase in BMD [15][16][17][18].…”
Section: Discussionmentioning
confidence: 74%
“…Therefore, elevated levels of TNF-alpha, which are observed in the serum of patients with psoriasis, may also result from the severe inflammatory process in psoriasis as well as from the contribution of other cells in the synthesis of this cytokine [63]. It is interesting that several research studies have shown increased body weight in patients with psoriasis after therapy with anti-TNF--alpha agents [140][141][142].…”
Section: Tumor Necrosis Factor-alpha (Tnf-alpha)mentioning
confidence: 99%
“…As an example, etanercept (chimeric soluble TNF receptor 2) or infliximab (anti-TNF monoclonal antibody) were reported to increase body weight and lean body mass in patients with rheumatoid arthritis (Briot et al, 2005). Such observation however, was not confirmed by a different study (Marcora et al, 2006).…”
Section: Inhibition Of Cytokine Productionmentioning
confidence: 98%